2020
DOI: 10.1007/s10940-020-09480-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Repeatedly Extorted Businesses Different? A Multilevel Hurdle Model of Extortion Victimization

Abstract: Objectives Research consistently shows that crime concentrates on a few repeatedly victimized places and targets. In this paper we examine whether the same is true for extortion against businesses. We then test whether the factors that explain the likelihood of becoming a victim of extortion also explain the number of incidents suffered by victimized businesses. The alternative is that extortion concentration is a function of event dependence. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 160 publications
0
5
0
Order By: Relevance
“…In this study, homicide data have been analysed from temporal, spatial and spatio-temporal point of view. The fundamental hypothesis is that the ‘where and when’ crimes are committed are not random but follow a clustered pattern [ 65 , 66 ] concentrated on a small proportion of places [ 67 ]. Therefore, GIS provides a powerful tool to identify existing patterns of crimes and their spatio-temporal patterns (high-risk areas), something which is essential for the development of strategies for reducing crime [ 68 – 72 ].…”
Section: Methodological Literature Reviewmentioning
confidence: 99%
“…In this study, homicide data have been analysed from temporal, spatial and spatio-temporal point of view. The fundamental hypothesis is that the ‘where and when’ crimes are committed are not random but follow a clustered pattern [ 65 , 66 ] concentrated on a small proportion of places [ 67 ]. Therefore, GIS provides a powerful tool to identify existing patterns of crimes and their spatio-temporal patterns (high-risk areas), something which is essential for the development of strategies for reducing crime [ 68 – 72 ].…”
Section: Methodological Literature Reviewmentioning
confidence: 99%
“…Our discussion is based on Section 5.6 of Stan Development Team (2022a), which also covers the related class of zero-inflated models (Lambert, 1992). Estévez-Soto et al (2021) presented a recent use of the hurdle model in criminology. To clarify this model let us assume, for the moment, that our data are the total number of offenses y 1 , .…”
Section: The Hurdle Modelmentioning
confidence: 99%
“…Results are presented in frequency distribution tables and the cumulative distribution is presented using Lorenz curves. The cumulative distribution is then compared with a Poisson-simulated distribution, estimated by a Monte Carlo simulation of a Poisson process with 500 replicates (see Estévez-Soto et al, 2021). Gini coefficients are also reported as an additional way to quantify burglary concentration, for which a figure of zero indicates no concentration and a figure of one indicates complete concentration.…”
Section: Analytical Strategymentioning
confidence: 99%
“…Gini coefficients are also reported as an additional way to quantify burglary concentration, for which a figure of zero indicates no concentration and a figure of one indicates complete concentration. To examine if the observed distribution statistically differs from a reference distribution (i.e., the aforementioned Poisson distribution), we use one-sample Kolmogorov-Smirnov (KS) tests (Arnold & Emerson, 2011;Estévez-Soto et al, 2021). It is noted that since the frequency of victimization is discrete and the victimization population in the 2015 TAVS (n = 194) was greater than a suggested sample size of 30 (Dimitrova et al, 2017), the KS test is suggested to be performed using an improved R package 'KSgeneral' (Dimitrova et al, 2020).…”
Section: Analytical Strategymentioning
confidence: 99%